Nanoplasmonic electron acceleration by attosecond-controlled forward rescattering in silver clusters. Issue 1 (December 2017) - Passig, Johannes; Zherebtsov, Sergey; Irsig, Robert; Arbeiter, Mathias; Peltz, Christian; Göde, Sebastian; Skruszewicz, Slawomir; Meiwes-Broer, Karl-Heinz; Tiggesbäumker, Josef; Kling, Matthias; Fennel, Thomas
Abstract In the strong-field photoemission from atoms, molecules, and surfaces, the fastest electrons emerge from tunneling and subsequent field-driven recollision, followed by elastic backscattering. This rescattering picture is central to attosecond science and enables control of the electron's trajectory via the sub-cycle evolution of the laser electric field. Here we reveal a so far unexplored route for waveform-controlled electron acceleration emerging from forward rescattering in resonant plasmonic systems. We studied plasmon-enhanced photoemission from silver clusters and found that the directional acceleration can be controlled up to high kinetic energy with the relative phase of a two-color laser field. Our analysis reveals that the cluster's plasmonic near-field establishes a sub-cycle directional gate that enables the selective acceleration. The identified generic mechanism offers robust attosecond control of the electron acceleration at plasmonic nanostructures, opening perspectives for laser-based sources of attosecond electron pulses. Accelerating electrons to high energy and controlling their properties on ultrafast timescales is challenging. Here the authors show controlled acceleration of electron bunches using forward scattering in the resonantly enhanced polarization field of silver clusters driven by a phase-tuned two-color laser field.